RELIGIOFIKASI KOMODITAS DAN IDENTITAS AGAMA ANAK MUDA KOTA SURABAYA - Ali Aziz (Al'Adalah, 2015)
There is three problem which will be studied in this research, that is (1) the meaning of religion, (2), the process of religious identity of young (3) process of religious identity mediatization through commodity religiofication. Third the problem, studied through qualitative descriptive method by phenomeno-logical perspective. From study result is obtained as follows. Firstly, the meaning of religion by SKI activist directed at the growing awareness of reason, which in turn meaning of religion is not limited to mere ritual ansich, but religion as way of life. Second. Process of reasoning awareness constructing through a islamic mentoring have been able to islamic representation to meet islamic young-ers. Third, process of religious identity mediatization through religiofication commodities is a form of religious expression. That process led to the estab-lishment of islamic pride that manifest it self in the totality of behavior. In the process it happen “shedding” taste, emotions and islamic motives are mediated in an islamic accessories (religiofication commodities). By usig the expression islamic accessories be envisaged, whic would make them as a symbols of islam to the others.